Reconstitution of the immunological defence and Candida albicans infection in oral mucosa of HIV+ patients under HAART - Santo, Marinho Del (Journal of Oral Diagnosis, 2016)
The HIV infection is a worldwide spread disease which with the HAART (highly active antiretroviral therapy) application has became a chronicle disease.The HAART promotes the reduction of the HIV viral load and partial and temporary reconstitution of the immunological defence system of the HIV-infected subject, although for that its toxicity and patient adherence to the treatment might be well monitored.With the HAART, the past high prevalence of oral and oropharyngeal lesions decreased significantly, although in a non-homogeneous pattern.The fungus Candida albicans is a commensal microorganism of the human gut tract which provokes an opportunistic infection, when there is an imbalance between its virulence and the defence conditions of the host.The pathogenicity of the Candida albicans influences the degree of opportunistic infection; however, the fungical colonization is mainly dependent of the current immunological status of the patient.The host defence against Candida albicans is also provided by non-immunological barriers, physical as the keratinocytes of the oral epithelium, serological as the neutrophils, polymorphonuclear leukocytes and macrophages or humoral as the saliva, although the role of the salivary immunoglobulins is still unclear. Independently of the immunosuppression, the sensitive control to balance immunological innate and immunological acquired actions is complex and it prevents against an indiscriminate immunological acquired response. Dendritic cells and lymphocytes are the main defensive immunological cells of the oral mucosa. The dendritic cells phagocytise and deplete microorganisms, presenting the products of such depletion as antigens to the T lymphocytes, which provide acquired immunological defence for excellence. Specific Th1 type provides cell-mediated immunological protection against Candida albicans and other pathogens. Moreover, Th2 type cells provide immunological tolerance against external and auto-antigens. Treg and Th17 cells are actors of vital importance in the switching between Th1 type and Th2 type responses, although the complete understanding of their roles in this balance is still an ongoing process.